Clinical and electromyographic criteria for the diagnosis of hereditary myotonic syndromes - V. P. Fedotov; S. A. Kurbatov; E. A. Ivanova; N. M. Galeeva; A. V. Polyakov (Нервно-мышечные болезни, 2015)
Hereditary myotonic syndromes (HMS) are a group of genetically heterogeneous diseases of the chlorine and sodium ion channels (channelopathies) with evident clinical polymorphism and high prevalence in the population. The differential diagnosis of early‑stage NMS poses a challenge to clinicians to this day. The investigation has attempted to elaborate informative differentiating criteria on the basis of a clinical and electromyographic study of 2 groups of patients with hereditary Thomsen or Becker myotonia (n = 45) and myotonic dystrophy type 1 (n = 39) verified by DNA analysis of the CLCN1 and DMPK genes. Along with the clinical symptoms, there may be the value of M‑response amplitude decrement in rhythmic stimulation of the n. ulnaris and the duration of myotonic discharges at pin electromyography of the m. tibialis anterior.